Color Changes Of Discolored Human Teeth After Immersion In Spinach Extract In Different Durations - Sefty Aryani Harahap; Lasminda Syafiar; Kristin Halim (Sriwijaya Journal of Dentistry, 2022)
Introduction: Recently, natural dental bleaching agents are being developed to replace chemical dental bleaching agents. Chemical dental bleaching agents containing hydrogen peroxide have the potential to cause toxicity as a side effect. Spinach leaves are natural ingredients that contain oxalic acid which can whiten teeth. Purpose: To investigate the color changes in discolored human teeth after immersion in spinach extract in different durations. Methods: 30 human premolar samples were divided into 3 groups, group A (immersion in 28 hours), group B (immersion in 42 hours), and group C (immersion in 56 hours). All 30 samples were discolored with coffee solution for 12 days and color status (L1, a1, b1) were measured using the chromameter. Then, each 10 samples were immersed in spinach extract according to their treatment group, and the color status (L2, a2, b2) were measured again. Color changes (∆E) were calculated with a formula concerning L, a, b data measured. Results: A significant color change is observed between group A, group B, and group C (p-value= 0.002), and further comparison between three groups showed that group A differed significantly with group C (p-value=0.000), group B also showed significant difference with group C (p-value=0.038). However, there was no significant difference between group A and group B (p-value=0.121). Conclusion: The significant color changes can only be observed after 56 hours of immersion. The spinach leaf extract has the potential to be used as a natural dental bleaching agent.